2010
DOI: 10.1590/s0004-282x2010000500010
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining quality of life in multiple sclerosis: fact, fiction, or limited reality?

Abstract: Health-related quality of life (HRQOL) is an important marker for health-related impacts on individuals with chronic diseases. This HRQOL study compares multiple sclerosis (MS) patients to a socio-demographically-matched healthy control group. HRQOL was assessed by means of a modular instrument (DEFU/DEFIS), which allows comparisons between diseased and healthy individuals. Main goal of the study was to obtain pertinent data to build a more reliable theoretical framework concerning HRQOL in MS. Another aim was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Cognitive problems, both the subjective experience of cognitive decline and objectively documented decline, are common among people with MS, and are associated with worse psychosocial and physical quality of life 47,48,27 . Although we expected fatigue to be the strongest predictor of daily outcomes, we did expect that days of slow or foggy thinking might be related to worse affective and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive problems, both the subjective experience of cognitive decline and objectively documented decline, are common among people with MS, and are associated with worse psychosocial and physical quality of life 47,48,27 . Although we expected fatigue to be the strongest predictor of daily outcomes, we did expect that days of slow or foggy thinking might be related to worse affective and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The results are in agreement with previous studies that have identified depression as the main predictor of HRQOL. 9 , 16 , 22 , 23 However, a smaller number of studies have also shown anxiety as another strong predictor for HRQOL. 5 , 24 Interestingly, the effect of depression and anxiety on physical as well as psychological subdomains were unequal, with depression having the stronger effect on all these subdomains, further suggesting the widespread negative effect of depression, and to a lesser extent anxiety, on multiple domains and accounting for its overall negative effect on the overall HRQOL in pwMS.…”
Section: Discussionmentioning
confidence: 99%
“… 8-10 To this effect, recent studies indicated the prevalence and incidence of depression and anxiety in pwMS, calling for improved screening, diagnosis and a more holistic patient care. 3-5 In most study findings, depression, along with other clinical symptoms such as fatigue, is found to be the strongest predictor of lower QOL in pwMS; 9 , 15 , 16 although some studies have found anxiety to be a more powerful predictor of QOL. 5 In general, such findings underscore the importance of recognizing comorbid psychiatric disorders in pwMS and call for the need to effectively screen and offer treatment options to these patients.…”
Section: Introductionmentioning
confidence: 93%
“…(15,16) Fatigue is a common and debilitating symptom of MS, and often has a negative impact on quality of life. (17,18,19) In Brazil, the studies conducted in São Paulo, show prevalence rate of approximately 5/100,000, (20) is considered a low prevalence country. Women are committed more often and the symptoms usually appear between 20 and 40 years, with peak incidence around 30 years.…”
Section: Introductionmentioning
confidence: 99%